Discerning The Lay Ignatian Vocation: The Christian Life Community - Muruzábal, Isabel (The way, 2025)
The article focuses on the development and mission of the Christian Life Community (CLC) as a lay Ignatian movement rooted in the spirituality of St Ignatius of Loyola. Topics include the historical evolution from early Jesuit-inspired lay groups to CLC, the role of discernment and spirituality in lay vocations, and the commitment to social engagement and ecclesial co-responsibility in contemporary society.